Report on MFS national review and planning meeting, Malawi - Homann-Kee Tui, Sabine; Mwale, Emmanuel; Ndibalema, Gloriana; Chimunya, Vimbayi; Okoth, John; Liben, Feyera; Chiduwa, Mazvita (International Institute of Tropical Agriculture, 2023)
The One CGIAR initiative on Mixed Farming Systems (MFS) entered its 1st year after its official inception in Malawi. Various partners that included the National Agricultural Research and Extension Systems (NARS), and the CGIAR researchers converged in Lilongwe, Malawi, to among other things; share, learn, assess progress, achievements, challenges, gaps, and opportunities, and to develop a strategy on system integration, gender, and social equity across work packages, research sites, and disciplines to support MFS outcomes and deliverables.